Deep phenotyping of the 5xfAD mouse model by MODEL‐AD: Development of new models and analysis methods/validation of pre‐clinical methods. (7th December 2020) - Forner, Stefania; ,
Abstract: Background: The Model Organism Development and Evaluation for Late‐Onset Alzheimer's Disease (MODELAD) has been established as a consortium consisting of University of California Irvine, University of Indiana, University of Pittsburgh, Jackson Laboratory and Sage Bionetworks to develop the next generation of Alzheimer's disease (AD) models and institute a standardized and rigorous process for characterization of animal models. One of the goals is to further characterize and deep phenotype well utilized early onset AD models, such as the 5xfAD model. This model is known for recapitulating many AD‐related phenotypes and have a relatively early and aggressive presentation. Method: Behavioral assays, Long‐term potentiation (LTP) recordings from acute hippocampal slices, RNA‐seq, immunofluorescent histology, and biochemical assays were performed in male/female 5xfAD mice and compared to age‐matched littermates (C57BL/6J) mice at 4, 8, 12 and 18 months. Result: 5xfAD mice exhibit robust plaque deposition, present throughout the brain by 4 months of age, with plaque numbers and sizes increasing with age, alongside increases in detergent soluble and insoluble Aβ38, Aβ40 and Aβ42 levels in both hippocampus and cortex. Concomitant with plaque deposition are increases in microglia densities, and expression of GFAP by astrocytes. Reductions in NeuN+ neurons are seen from 4 months of age in the cortex. Female mice show increased plaque and Aβ burden, and associated changes in glial cells, compared to male mice, but this may be due to observed increased transgene expression from the Thy1 promoter in female mice. Strong behavioral deficits are seen in the elevated plus maze from 4 months of age, compared to wild‐type controls, as well as robust LTP deficits. Conclusion: In summary, 5xfAD mice have a range of cognitive and motor deficits and severe amyloid pathology. All data sets and protocols will be made widely available to the scientific community. For more information, see model‐ad.org.